About Trinocladus Raineri, 1922: when some Permocalculus (Gymnocodiacean algae) reveal to be Triploporellacean algae (Revision of the Jesse Harlan Johnson Collection. Part 5) - Granier, Bruno; Bucur, Ioan I.; Dias-Brito, Dimas [UNESP] (Springer Nature, 2017)
The Upper Cretaceous-Paleogene genus Trinocladus that is based on T. tripolitanus Raineri, 1922, originally described from Libyan material, is morphologically well constrained. Its species are commonly distinguished on the basis of their biometrics. However, the narrow Gaussian distribution reported for some measurements may result from post-mortem dynamic sorting as suggested by a review of the surrounding microfacies. An examination of Brazilian material of the type-species suggests a slightly club-shaped thallus morphology. Two “false Permocalculus” species originally described by Johnson and the type-material of which has been reexamined are formally reascribed to the genus Trinocladus. T. budaensis, the smallest one, has slightly club-shaped thallus, too. T. elliotti is poorly mineralized and insufficiently documented. In addition to T. tripolitanus, Raineri described a tiny species which was later revised by Pia, i.e., Dissocladella ondulata. D. bonardii, a name recently introduced by Radoičić et al. and which is based on Raineri’s original material, is considered here as an objective junior synonym of D. ondulata.
Keywords: Biometric limitation; Cretaceous; Dasycladales; Dissocladella; Trinocladus